Jacob Rabinowitz, The Rotting Goddess: The Origin of the Witch in Classical Antiquity’s Demonization of Fertility Religion - Jones, Ieuen (Pomegranate, 2007)
Jacob Rabinowitz, The Rotting Goddess: The Origin of the Witch in Classical Antiquity’s Demonization of Fertility Religion (Brooklyn, NY: Autonomedia, 1998), 153 pp., 14.00 (paper).